Media literacy's role toward Roda Jari Mas Radio listeners in dealing with disasters - Sjuchro, Dian Wardiana; Khadijah, Ute Lies Siti; Viannisa, Nadhifa; Lavigne, Franck (Jurnal Kajian Informasi dan Perpustakaan, 2024)
Pangandaran is an area that is vulnerable to tsunami disasters. It is caused the sonic activity of the Indo-Australian plate’s in the southern coastal regio. Roda Jari Mas (RJM) Radio as a community radio has the role of informing the community about tsunami disaster information. This study aims to determine the role of media literacy for RJM Radio listeners in dealing with disasters in Pangandaran Regency. This research used a qualitative approach with a case study research method through Focus Group Discussion (FGD) on 9 participants. The results stated that the most widely used media exposure of Pangandaran people is radio, which is RJM Radio, television, and social media. Sources of disaster information obtained by the Pangandaran community include television and social media (if a disaster occurs). There are three aspects influenced people's readiness to face disasters, namely media exposure, government attention, and infrastructure. Social media can be a source of disaster information. The community has participated in several disaster mitigation simulations, but has not been supported by adequate infrastructure. The conclusion of the study is that the Pengandaran community has low media exposure could have an impact on a lack of knowledge and low levels of government attention, which resulted in a lack of disaster preparedness training, not to mention low levels of infrastructure. All of these things had a big impact on one thing, namely low preparedness to face disasters.